Case Report: Management of a BCR-ABL1-positive high-risk rhabdomyosarcoma patient using tyrosine kinase inhibitors - Li, Fan; Jiang, Dapeng; Liu, Yu; Yin, Minzhi; Zhong, Yumin; Xu, Min; Zhang, Anan; Han, Yali (Frontiers in Medicine, 2025)
Rhabdomyosarcoma represents a prevalent type of soft tissue sarcoma encountered in pediatric patients. Despite multimodal intensified therapies encompassing surgical intervention, chemotherapy, and radiotherapy, the prognosis for patients with high-risk rhabdomyosarcoma remains notably unfavorable. To date, no definitive and efficacious molecularly targeted therapies have been established. This report describes the first documented case of a rhabdomyosarcoma patient harboring a positive BCR-ABL1 fusion gene. At the time of initial diagnosis, the patient presented with a primary tumor in the right thigh and extensive metastatic involvement affecting both lungs, pleura, mediastinum, pelvic cavity, and the right inguinal region, resulting in the classification of the case as high-risk. In addition to conventional multimodal therapy, early intervention using tyrosine kinase inhibitors was implemented, leading to the achievement of an early complete response.